Significance of metallothioneins in differential cadmium accumulation kinetics between two marine fish species. (May 2018) - Le Croizier, Gaël; Lacroix, Camille; Artigaud, Sébastien; Le Floch, Stéphane; Raffray, Jean; Penicaud, Virginie; Coquillé, Valérie; Autier, Julien; Rouget, Marie-Laure; Le Bayon, Nicolas; Laë, Raymond; Tito De Morais, Luis
Abstract: Impacted marine environments lead to metal accumulation in edible marine fish, ultimately impairing human health. Nevertheless, metal accumulation is highly variable among marine fish species. In addition to ecological features, differences in bioaccumulation can be attributed to species-related physiological processes, which were investigated in two marine fish present in the Canary Current Large Marine Ecosystem (CCLME), where natural and anthropogenic metal exposure occurs. The European sea bass Dicentrarchus labrax and Senegalese sole Solea senegalensis were exposed for two months to two environmentally realistic dietary cadmium (Cd) doses before a depuration period. Organotropism ( i.e., Cd repartition between organs) was studied in two storage compartments (the liver and muscle) and in an excretion vector (bile). To better understand the importance of physiological factors, the significance of hepatic metallothionein (MT) concentrations in accumulation and elimination kinetics in the two species was explored. Accumulation was faster in the sea bass muscle and liver, as inferred by earlier Cd increase and a higher accumulation rate. The elimination efficiency was also higher in the sea bass liver compared to sole, as highlighted by greater biliary excretion. In the liver, no induction of MT synthesis was attributed to metal exposure, challenging the relevance of using MT concentration as a biomarker of metal contamination. However, the basal MT pools were always greater in the liver of sea bass than in sole. This species-specific characteristic might have enhanced Cd biliary elimination and relocation to other organs such as muscle through the formation of more Cd/MT complexes. Thus, MT basal concentrations seem to play a key role in the variability observed in terms of metal concentrations in marine fish species. Graphical abstract: Image 1 Highlights: Environmentally realistic trophic Cd doses led to accumulation in edible marine fish. Faster accumulation occurred in the sea bass liver compared to the sole liver. Muscular Cd accumulation was also higher in sea bass than in sole. MT concentrations failed to reflect Cd exposure in both species. Species-specific basal MT pools seemed to be one of the physiological factors influencing Cd accumulation and elimination. Abstract : Two marine fish species were chronically exposed to environmentally realistic trophic Cd doses. Species-specific basal MT pools seemed to be one of the physiological factors influencing Cd accumulation and biliary excretion.